Awareness and Perception of People Towards Mutual Funds at Coimbatore City - Devasenathipathi, T.; Saleendran, Dr. P. T.; Shanmugasundram, Dr. A. (Indian Journal of Finance, 2007)
Today’s Indian financial services segment encompasses a whole gamut of services like Insurance, Mutual fund, Capital market, Derivatives market and equity market. The Mutual Fund is an investment vehicle for investors who pool their saving for investing in diversified range of securities with the aim of gorgeous yields and appreciation in their value. Now-a -days Mutual funds attracted most of the socio-economic classes because peoples sensing that Investment is vital part of every human beings life as well as they expect fast return even while there is few investment decision risks. People are highly influenced by these mutual funds companies’ new schemes and different services. But success of Mutual fund companies depends on Consumer awareness, perception, demographic and geographic factors. Hence, an attempt was made to know Coimbatore based investors awareness, investment option, purpose of investment etc.For this study Consumer opinions are collected and the data is analyzed to determine awareness and perception of people towards Mutual Funds at Coimbatore city.